2009
DOI: 10.1152/japplphysiol.91657.2008
|View full text |Cite
|
Sign up to set email alerts
|

Improved predictive models for plasma glucose estimation from multi-linear regression analysis of exhaled volatile organic compounds

Abstract: Lee J, Ngo J, Blake DB, Meinardi S, Pontello AM, Newcomb R, Galassetti PR. Improved predictive models for plasma glucose estimation from multi-linear regression analysis of exhaled volatile organic compounds. J Appl Physiol 107: 155-160, 2009. First published May 7, 2009 doi:10.1152/japplphysiol.91657.2008.-Exhaled volatile organic compounds (VOCs) represent ideal biomarkers of endogenous metabolism and could be used to noninvasively measure circulating variables, including plasma glucose. We previously demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 28 publications
3
56
0
5
Order By: Relevance
“…As mentioned in the previous section, some studies found different correlations between blood glucose and exhaled breath, with a regression coefficient range from 0.08 to 0.98 [32][33][34][35][36][37][38][39][40]. Yet, in our study we found a negative correlation towards higher acetone concentrations when blood glucose concentrations declined, with a regression coefficient of only 0.52.…”
Section: Discussionsupporting
confidence: 49%
“…As mentioned in the previous section, some studies found different correlations between blood glucose and exhaled breath, with a regression coefficient range from 0.08 to 0.98 [32][33][34][35][36][37][38][39][40]. Yet, in our study we found a negative correlation towards higher acetone concentrations when blood glucose concentrations declined, with a regression coefficient of only 0.52.…”
Section: Discussionsupporting
confidence: 49%
“…These hydrocarbons have been detected in the exhaled human breath [19][20][21][22][23][24][25], and have been proposed as a means of assessing in vivo lipid peroxidation. Specifically, higher levels of exhaled acetone were observed in association with diabetes [22]. Additionally, increases in ethane concentration was observed from rat hepatocytes in the presence of oxidants [26].…”
Section: Discussionmentioning
confidence: 99%
“…Nelson et al also reported no difference in isoprene levels between healthy controls and diabetes patients and no statistical difference between diabetes patients in the fasting and postinsulin state [178]. A few studies showed that methyl nitrate as well as ethanol, acetone and aromatic hydrocarbons have been correlated with blood glucose in patients with Type 1 diabetes [185][186][187]. Other compounds that can discriminate between healthy controls and patients with Type 2 diabetes include dimethyl sulfide, butanol and pyridine [188].…”
Section: Perspective | Calenic and Amannmentioning
confidence: 99%